Hemiparkinsonism associated with mesencephalic cavernoma: case report and review of literature - Dall’aglio Rocha, Carlos Eduardo; Nazaré Oliveira, Fábio de; Meguins, Lucas Crociati (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2011)
Parkinsonism is a movement disorder characterized by resting tremor, slow and decreased movements (hypokinesia and akinesia), rigidity, postural instability, problems with gait, and coordination. Parkinson's disease (PD) is the most common cause of parkinsonism and its prevalence is estimated to range from 0.1% to 0.3% in the general population and from 1% to 2% in persons 65 years of age or older. Although the majority of cases of PD are describe to be sporadic, many identifiable etiologies have been included as possible causes of parkinsonism, such as genetic disorders, cerebrovascular events and intoxication. However, mesencephalic cavernoma is an extremely rare condition associated to hemiparkinsonism. In the present report, we describe the case of a Brazilian woman that evolved symptoms of hemiparkinsonism and presented a ventral mesencephalic cavernoma on radiological investigation.
Keywords: Cavernous hemangioma; mesencephalon; Parkinson disease